Reconfigurable slots antenna based on mechanical movement for smart communication system - Saad, Muhammad Majdi (2021)
Nowadays, the increasing number of mobile users has exponentially increased mainly due to new applications’ demand by users, such as video streaming, media social communication applications, online banking or e-wallet, and multiplayer online gaming. Thus, the cellular provider needs to provide the best coverage direction to the specific clients. Radiation pattern reconfigurable antennas are a solution that enables changes in radiation pattern while maintaining the frequency bands based on the system requirements. Therefore, the objective of this research was to design a new reconfigurable co-planar waveguide (CPW) slot antenna based on parasitic element movement. All antennas were designed, simulated and analysed using Computer Simulation Technology (CST) Microwave Studio. Then, the antennas were fabricated in a fabrication laboratory. The next step was to measure the fabricated antenna for several parameters in the laboratory. The research started with an investigation of a multilayer slot on a microstrip patch antenna. The results showed that the multi-layer slot did not improve the bandwidth of the microstrip patch. By adding the three-shaped slot, it created a triple band as compared to only two bands obtained for the microstrip patch without 3-shaped slots. For example, for microstrip (MS) Antenna B1 and MS Antenna B2, they maintained the first resonant frequency at 2.52 GHz. For the second resonant frequency, they shifted from 5.01 GHz to 4.97 GHz and created a third band at 6.18 GHz. Next, the studies on the CPW slot antenna were done by using three different basic geometry slots, which consisted of a rectangular slot, a plus-shaped slot and a circular slot. In CPW Antenna C, it was shown that the effect of increasing the number of small rectangular slot from a single slot at CPW Antenna C1 to three slots at CPW Antenna C3 could improve 500 % for the second bandwidth of the resonant frequency from 120 MHz to 720 MHz and improve 88.36 % of return loss from 14.26 dB to 26.84 dB. It also changed the shape of the radiation pattern. In CPW Antenna F, the change of the T-slot location from CPW Antenna F1 to CPW Antenna F3 could affect the main lobe to change the direction that was opposite to each other. From the observation, for CPW Antenna I, the beam of the main lobes could be controlled or tuned from 900 to 2700 by changing the location of the single square parasitic element from CPW Antenna I1 to CPW Antenna I4. This also showed that at CPW Antenna L, the changes of slots could change the radiation pattern direction. For the first resonant of CPW Antenna L3 and CPW Antenna L4, it reflected the opposite main lobe direction changes. Besides that, the second resonant of CPW Antenna L3 and CPW Antenna L4 was also reflected to change to the opposite side of lobe direction. This design can be used for a developed smart antenna system for the future wireless communication system, such as a radar system.